FINANCIAL STATEMENT ANALYSIS TO EVALUATE THE FINANCIAL PERFORMANCE OF COMPANIES IN THE FOOTWEAR SUB-INDUSTRY LISTED ON THE INDONESIAN STOCK EXCHANGE - Dina Mariana Uli Lubis (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Financial reports are needed as accountability for the financial management carried out by the company, which provides various information that is useful for evaluating company performance. The study aims to identify and analyze financial ratios in the footwear sub-industry listed on the Indonesia Stock Exchange to obtain an overview of the company's financial performance. The data used in this study are secondary data in the form of company financial reports. Purposive sampling is used in this study, namely using the footwear industry sub-sector consisting of two companies, namely PT Sepatu Bata, Tbk and PT Primarindo Asia Infrastructure, Tbk. The data analysis method used is a comparative descriptive method, namely by describing and comparing certain characteristics or variables to obtain an overview and understanding of the problems studied. By using financial ratio analysis in the form of liquidity ratios and solvency ratios, it is found that both companies have liquidity ratios that tend to decrease as indicated by the calculation of the current ratio and acid test (or quick) ratio whose values ​​tend to decrease during the observation period, indicating that the company's ability tends to decrease to settle its short-term obligations. The solvency ratios used are the debt-to-equity ratio and the debt-to-total-assets ratio which show calculation results that tend to increase during the observation period, indicating that the company's financing carried out by creditors tends to increase in amount.